'There is no political agenda': Governing and contesting the compassionate city in Louisville. Issue 1 (2nd January 2019) - Ruez, Derek; Parekh, Trushna
Abstract : This paper examines the emerging trend for city governments to declare themselves compassionate. Opening up the 'compassionate city' as an object of critical scrutiny, we outline some of the key ways that compassion has been approached in critical scholarship before turning our attention to the politics of these urban commitments to compassion as they are enacted in practice. Focusing on the city of Louisville, where the 'compassionate city' imaginary has been taken on both by politicians and by economic, migrant and racial justice activists, we examine the potential of compassion as and in relation to other political grammars, and consider the polyvalent nature of the compassion as it has shaped public debate and political struggle in the city. We argue that this turn toward compassion should be evaluated and understood neither in terms of the good intentions of compassion proponents nor exclusively through analyses that reduce compassion to a single logic to be critiqued, but, instead, in terms of its contingent politics. In doing so, we respond to recent debates about the specificity of the political by emphasizing that the meaning of politics and the political grammars through which we understand urban problems are never the province of critical scholarship alone, and we highlight the value of approaches that can sensitize us to the ways that politics—and its meaning—can itself become a problem as the political nature of the compassionate city is called into question.